Sustainable open data ecosystems in smart cities: A platform theory-based analysis of 19 European cities - Lněnička, Martin; Nikiforova, Anastasija; Clarinval, Antoine; Luterek, Mariusz; Rudmark, Daniel; Neumaier, Sebastian; Kevic, Karlo; Bolivar, Manuel Pedro Rodriguez (Elsevier Science BV, 2024)
An understanding of how modern Open Data Ecosystems (ODEs) work is critical in the context of current trends towards sustainability and smartness, while is seen to be an asset to support urban governance and development, in coordinating actions, and fostering civic engagement. This paper aims to establish such understanding by analyzing the contextual patterns, platforms, and components shaping sustainable ODEs by employing platform theory. This study explores and compares characteristics, similarities, differences, and best approaches in 19 cities across 8 countries. In this study we (1) identify 50 patterns that influence and shape sustainable ODEs and their platforms, i.e., Open Data Platform Ecosystems (ODPEs); (2) explore the relationships between platforms and other ODPEs components by developing a respective model, and identifying internal platforms and other components; (3) empirically validate the conceptual findings of five types of ODPEs presented in the literature, redefining them from the conceptual to real-life implementation of the respective components in sample cities; (4) considering the experience gained during the study with respect to the ODPEs and external pressures and environments that shape or influence them, we define 12 recommendations for policy planning and urban governance of more sustainable ODEs.
Udržitelné ekosystémy otevřených dat v chytrých městech: Analýza 19 evropských měst založená na teorii platformy
Keywords: Open data ecosystem; Open data platform ecosystem; Smart city; Multi -country comparative study; Urban development; Urban governance; Ekosystém otevřených dat; Ekosystém otevřené datové platformy; Chytré město; Srovnávací studie pro více zemí; Rozvoj měst; Řízení měst